Data co-synthesis in developing public product service systems. Issue 2 (2nd April 2020) - Fridman, Ilya; Napper, Robbie; Roberts, Sarah
ABSTRACT: Design and research teams working on public product service systems (PPSS) are often confronted with large data sets, presented in a complex language. This paper presents a method for how designers may translate quantitative aggregated data with a toolkit that enables qualitative co-synthesis to generate novel PPSS proposals. The toolkit development and application is shown through a specific case study in Melbourne, Australia, that focused on reimagining a public transport bus service in light of emerging propulsion and information technologies. People affected by the service were able to assist in co-synthesising existing data from transport planning literature into emergent ideas for system upgrades or even complete overhauls. A variety of multi-faceted service interventions were developed through a series of workshops with different participant groups. Workshop outcome variations further support the notion of emergence in co-creation, and reinforce the importance of running multiple sessions due to their potential impact on project outcomes. This paper proposes that co-synthesising complex data with the help of a toolkit, which may be a powerful way to inform PPSS design. An application framework is presented to summarise this process and to generate discussion towards broader application and further refinement.